2020
DOI: 10.1111/aman.13392
|View full text |Cite
|
Sign up to set email alerts
|

Human Energy Expenditure in Anthropology and Beyond

Abstract: Humans have successfully inhabited every continent on this planet. Our ability to survive and thrive in such a wide range of environments is fascinating, particularly from an energetic perspective. As knowledge of human total energy expenditure (TEE, kcal day−1) has deepened, so too has the ability to interpret observable patterns in human metabolic physiology and apply these interpretations to our evolutionary history. This review examines the basic components of human TEE as well as the interactions among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 99 publications
(157 reference statements)
0
12
0
3
Order By: Relevance
“…2 Situational factors such as thermoregulation, growth and immune costs may further influence final TEE. 3…”
Section: Energy Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…2 Situational factors such as thermoregulation, growth and immune costs may further influence final TEE. 3…”
Section: Energy Homeostasismentioning
confidence: 99%
“…Factors such as larger meal sizes, intake of carbohydrate and protein as opposed to fat, and a low‐fat plant‐based diet can increase energy expenditure from TEF 2 . Situational factors such as thermoregulation, growth and immune costs may further influence final TEE 3 …”
Section: Energy Homeostasismentioning
confidence: 99%
“…We found that across all individuals, there was no significant difference in TEE (kcal day À1 ) from early to later in the course. Recent research by Ocobock (2016aOcobock ( , 2020 in similar expedition settings suggests that as relative "newcomers" to this kind of highly challenging environment, the continuous exposure to high levels of physical activity while undergoing novel and intense ecological stress, leads to sustained total energy expenditure at very high levels, well over ~4000 kcal day À1 , over weeks and months without any tapering of energetic costs (Ocobock, 2016a(Ocobock, , 2020. Averaging across, subjects in our study maintained estimated TEE at ~4000-6000 kcal day À1 from early to late in the course.…”
Section: Physical Activity Intensity and Energy Expenditure During Th...mentioning
confidence: 99%
“…Body mass fluctuation is more nuanced than the direct consumption/expenditure of calories and caloric intake and the macronutrient content consumed can help explain expenditure. However, the use of energy deposits and subsequent body composition changes can broadly point to energy expenditure exceeding energy intake and help infer energy status (Ocobock, 2020;Westerterp et al, 1992). When facing energy deficits, the body will preferentially burn fat stores and then begin to burn muscle (Ocobock, 2017) with likely functional implications for everyday activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation